A Framework for GPU-accelerated Virtual Cardiac Intervention - Yu, Rongdong; Chiang, Patricia; Chen, Wenyu; Zheng, Jianmin; Cai, Yiyu; Ye, Xiuzi; Zhang, Sanyuan; Zhang, Yin; Mak, Koon-Hou (International Journal of Virtual Reality, 2009)
Cardiovascular diseases is a major cause of deaths in many developed countries. To treat cardiovascular diseases, minimally invasive cardiac intervention is widely used as an effective yet complicated solution. Training of cardiac intervention thus plays a crucial role. This paper addresses the use of Virtual Reality (VR) technology for the simulated training of cardiac intervention. In particular, the paper describes the architecture of a simulation system for virtual cardiac intervention. The framework proposed consists of hardware component, software component and methodology component. As an enabling technology, Graphics Processing Unit (GPU) is applied in this work to enhance cardiac modeling, cardiac visualization, and cardiac interaction with the VR simulation environment